Affect of Operation Conditions of Triple Half Bridge Series Resonant Inverter for Harmonic Distortion and Power Factor - Sazak, Bekir Sami; Cetin, Sevilay (IEEE, 2010)
The main aim of this paper is to discusses the change in harmonic distortion and power factor by the variation of operation conditions of a triple half bridge series resonant inverter circuit (THB-SRI). THB-SRI topology allows the control of three outputs, simultaneously and independently, up to their rated powers saving component count compared with the three half bridge solution. Results of this study can be used as an aid in component selection and understanding the affect of operation conditions to the other circuit parameters. Details of the study are presented along with simulation results.
Keywords: Induction heating; PSpice; Power factor; THD; Engineering